Impact of Immunonutrition on T Cell Activation: A Randomized Control Study in Cardiac Surgery Patients - Svetikienė, Marija; Trybė, Dainius; Strioga, Marius; Veželienė, Jevgenija; Isajevas, Viktoras; Malickaitė, Radvilė; Jurgauskienė, Laimutė; Ringaitienė, Donata; Šerpytis, Mindaugas; Šipylaitė, Juratė (Acta medica Lituanica, 2021)
Background. Cardiac surgery provokes an intense inflammatory response that can cause an immunosuppressive state and adverse postoperative outcomes. We recently showed that postoperative immunonutrition with glutamine in “fragile” low-risk cardiac surgery patients was associated with a significantly increased level of CD3+ and CD4+ T cells. In order to clarify the biological relevance and clinical importance of these findings, we investigated whether an increase in the CD4+ T cell level was caused by changes in the systemic inflammatory response (caused by surgery or infection) and if it was associated with their activation status. Methods. A randomized control study of low operative risk but “fragile” cardiac surgery patients was performed. Patients were randomized into immunonutrition (IN) and control groups (C). The IN group received normal daily meals plus special immune nutrients for 5 days postoperatively, while the C group received only normal daily meals. Laboratory parameters were investigated before surgery and on the sixth postoperative day and the groups were compared accordingly. The expression of the CD69+ marker was investigated to determine T cell activation status. Serum concentrations of cytokines (interleukin-10 (IL-10), tumor necrosis factor α (TNF-α) and interleukin-6 (IL-6)) and C-reactive protein (CRP) were determined to assess the systemic inflammatory response, while procalcitonin (PCT) levels were evaluated to confirm or deny possible bacterial infection. Results. Fifty-five patients were enrolled in the study. Twenty-seven (49.1%) were randomized in the IN group. Results show that on the sixth postoperative day, the CD4+CD69+ and CD8+CD69+ counts did not differ between the IN and C groups, accordingly 0.25 [0.16–0.50] vs 0.22 [0.13-0.41], p=0.578 and 0.13 [0.06–0.3] vs 0.09 [0.05–0.14], p=0.178. Also, statistically significant differences were not observed in the cytokine levels (IN and C groups: TNF-α 8.13 [7.32–10.31] vs 8.78 [7.65–11.2], p=0.300; IL-6 14.65 [9.28–18.95] vs 12.25 [8.55–22.50], p=0.786; IL-10 5.0 [5.0–5.0] vs 5.0 [5.0–5.0], p=0.343 respectively), which imply that an elevated T cell count is not associated with the systemic inflammatory response. Also, PCT (IN and C groups: 0.03 [0.01–0.09] vs 0.05 [0.03–0.08], p=0.352) and CRP (IN and C groups 62.7 [34.2–106.0] vs 63.7 [32.9–91.0], p=0.840) levels did not differ between the two groups. Moreover, low levels of PCT indicated that the increase in T cell count was not determined by bacterial infection. Conclusions. Our findings showed that CD4+ T cell levels were associated with neither the systemic inflammatory response nor bacterial infection. Secondly, increases in T cells are not accompanied by their activation status. These results suggest a hypothesis that a higher postoperative T cell concentration may be associated with postoperative immunonutrition in low-risk cardiac surgery patients with intact cellular vitality, i.e. “fragile”. However, immunonutrition alone did not affect T cell activation status.